2011
DOI: 10.1038/ejhg.2011.95
|View full text |Cite
|
Sign up to set email alerts
|

Duplication at chromosome 2q31.1-q31.2 in a family presenting syndactyly and nystagmus

Abstract: HOXD genes encode transcription factors involved in the antero-posterior patterning of the limb bud and in the specification of fingers. During the embryo development, HOXD genes are expressed, following a spatio-temporal colinearity that involves at least three regions, centrometric and telomeric to this cluster. Here, we describe a father and a daughter presenting a 3-4 hand bilateral syndactyly associated with a nystagmus. Array-comparative genomic hybridisation showed a 3.8 Mb duplication at 2q31.1-q31.2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Two such duplications are associated with mesomelic dysplasia (a shortening of the forearm and lower leg), whereas a third and larger duplication causes syndactyly (fused digits) (21)(22)(23). Such distinct clinical outcomes as well as the present report illustrate the difficulty in elucidating those molecular mechanisms underlying the pathological consequences of complex genetic conditions in humans in the absence of a proper and adapted animal model.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Two such duplications are associated with mesomelic dysplasia (a shortening of the forearm and lower leg), whereas a third and larger duplication causes syndactyly (fused digits) (21)(22)(23). Such distinct clinical outcomes as well as the present report illustrate the difficulty in elucidating those molecular mechanisms underlying the pathological consequences of complex genetic conditions in humans in the absence of a proper and adapted animal model.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to deletions, other rearrangements, such as inversions, translocations, or duplications involving sequences flanking the gene cluster, are observed in human patients, which are often linked to various limb anomalies (20)(21)(22)(23) (Fig. 1A).…”
mentioning
confidence: 99%
“…It has also been found that minimal duplication does not seem to cause the phenotypical deformity [ 72 ]. Since its finding, HOXD13 has been linked with multiple limb deformities including SD type V, brachydactyly and syndromic forms of syndactyly [ 73 , 74 ].…”
Section: Syndactyly: the Genetic Search And A Problem For Clinical CLmentioning
confidence: 99%
“…Duplications of the HOXD cluster have been identified in rare patients. A 3.8 Mb large duplication at 2q31.1q31.2 comprising 27 genes including the entire HOXD cluster has been identified in a father and his daughter presenting with bilateral hand syndactyly and nystagmus [32]. A second patient with a 2q24.3q32.1 duplication presented with early-infantile-onset epilepsy, hypoplastic left heart syndrome, and global developmental delay [33].…”
Section: Discussionmentioning
confidence: 99%